The Transition From MoS2 Single-Layer to Bilayer Growth on the Au(111) Surface - Ewert, Moritz; Buß, Lars; Braud, Nicolas; Kundu, Asish K.; Sheverdyaeva, Polina M.; Moras, Paolo; Genuzio, Francesca; Menteş, Tevfik Onur; Locatelli, Andrea; Falta, Jens; Flege, Jan Ingo (Frontiers in Physics, 2021)
The transition from single-layer to bilayer growth of molybdenum disulfide on the Au(111) surface is investigated by in situ low-energy electron and photoemission microscopy. By mapping the film morphology with nanometer resolution, we show that a MoS2 bilayer forms at the boundaries of single-layer single-domain MoS2 islands and next to merging islands whereas bilayer nucleation at the island centers is found to be suppressed, which may be related to the usage of dimethyl disulfide as sulfur precursor in the growth process. This approach, which may open up the possibility of growing continuous films over large areas while delaying bilayer formation, is likely transferable to other transition metal dichalcogenide model systems.